Development of a Complex Intervention to Improve Adherence to Antidiabetic Medication in Older People Using an Anthropomorphic Virtual Assistant Software - Félix, Isa Brito; Guerreiro, Mara Pereira; Cavaco, Afonso; Cláudio, Ana Paula; Mendes, Anabela; Balsa, João; Carmo, Maria Beatriz; Pimenta, Nuno; Henriques, Adriana (Frontiers in Pharmacology, 2019)
Introduction: Improving adherence to antidiabetic medication is crucial, resulting in improved health outcomes, cost reduction and minimization of waste. A lack of underlying theory in existing interventions may explain the limited success in sustaining behavior change. This paper describes the development of a theory and evidence-based complex intervention to improve adherence to oral antidiabetics in older people via a software prototype with an anthropomorphic virtual assistant. Methods: The Behaviour Change Wheel (BCW) was used to develop a theoretical understanding of the change process, corresponding to the first phase of the Medical Research Council Framework for developing and evaluating complex interventions. At the BCW core is a model of human behavior (COM-B), which posits that human behavior (B) results from the interaction between capabilities (C), opportunities (O) and motivation (M). Literature-derived medication adherence determinants were mapped onto COM-B components. Then, intervention functions (IFs) were selected employing the APEASE criteria. Finally, standardized behavior change techniques (BCTs) were chosen based on their suitability and their effectiveness on medication adherence trials. The prototype was developed for android devices; its core was implemented in Unity3D, using a female 3D virtual assistant, named Vitória. Results: Two COM-B components were identified as main targets for behavior change – psychological capability and reflective motivation; these were linked with four IFs – education, persuasion, enablement and environmental restructuring. Eleven BCTs were, in turn, linked with the IFs. An example of a BCT is “Problem solving”; it requires users to pinpoint factors influencing non-adherence and subsequently offers strategies to achieve the desired behavior. BCTs were operationalized into the dialogues with Vitória and into supplementary software features. Vitória communicates with users verbally and non-verbally, expressing emotions. Input options consist of buttons or recording values, such as medication taken. Conclusion: The present approach enabled us to derive the most appropriate BCTs for our intervention. The use of an explicit bundle of BCTs, often overlooked in interventions promoting medication adherence, is expected to maximize effectiveness and facilitates replication. The first prototype is being refined with users and health professionals’ contributions. Future work includes subjecting the prototype to usability tests and a feasibility trial.